ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN TELUR AYAM RAS DI KOTA KENDARI DAN HUBUNGANNYA DENGAN KEBERDAYAAN PETERNAK - Ine Fausayana; Marwan Akbar Marzuki (Universitas Halu Oleo, 2016)
This study aimed to determine : 1).Factors that affect demand for broiler chicken eggs in Kendari city, 2) The empowerment of broiler breeders, 3) The correlation between demands for broiler chicken eggs and the empowerment of broiler breeders. The study employed an associative (cause-effect) design. Simple of chicken eggs consumers were determine purposively (purposive sampling) involving 50 consumers of broiler chicken eggs, whereas breeders empowerment was sample by using a census / total sampling method, thereby including all 5 breeders of broiler chicken. Data were collected by administering questioneair and study document. The data were analyzed by performing a descriptive statistical analysis and multiple linear regression. Result of the study concluded that : 1) consumers taste price of broiler chicken eggs, price of subtitusing goods, consumers, income, and the number of people and household were among the factors which collectively had a significant effect on the demand for broiler chicken eggs, 2) breeders of broiler chicken habe been increasingly empowered not only in the aspects of changes in worker, capital, productions but also income and profits, 3) demand for broiler chicken eggs had a positive correlations to the empowerment of chicken farmers, althougt the correlations only satisfied a very weak criteria.Keywords : Breeders, broiler chicken eggs, demand, , Factors affecting, empowerment.